School History as a Method of Formation of Political Consciousness in Contemporary France - N. V. Litvak (Vestnik MGIMO-Universiteta)
The article discusses the attitude of the ruling elite in modern France to the school teaching of history, as the primary method of formation of political consciousness and outlook of the new generations. To achieve these purposes the complex of scientific and political methods is created. The programs are constantly changing, reflecting the general political struggle in French society, whose protagonists seek the arguments in support of their positions in history. In this context, the school programs are periodically in focus of urgent debates, and each their change is a compromise. The political approach is to form a state point of view of history, recorded in the programs required to study in schools. Those programs include a carefully selected set of topics, facts and personalities to be studied. In addition, the internal political struggle is coming not just about the form but the content too. In particular, for a number of years in the program a separate theme "Islam"is included, but not, for example, the theme "Christianity." However, supporters of the preservation of study of the Christian contribution to the history and the culture of France retain extensive relevant material included in a number of various subjects not directly devoted to Christianity. Informational approach to education is that the resources of the psyche and student's instructional time are very limited. The freedom of school teachers to refer to historical sources and even to interpret them within the broad framework is formally proclaimed. However, a program and a limited time to study it in conjunction with the responsibility of teachers for the results of their work, checked in exams, in fact does not leave them enough time to study an other point of view that goes beyond the official program.